A research on trust triggers in the context of B2C online shopping - Abd Ghaffar, Nariemah (2010)
Trust has become a critical factor in simulating purchases over the Internet. Therefore, building trust of consumers in e-commerce transaction has been the important task for the business merchant to look for. For the website designer, it is really essential for them to identify the elements that can trigger trust among consumers to shop online. In this research, the aim is to understand the notion of trust triggers in the context of online shopping. There are two objectives in this research. The first objective is to identify the different types of trust triggers in an online shopping environment while the second objective is to identify the perceptions of trust triggers among consumers in an online shopping environment. This research is significant to the business merchant who conducting their business in online environment and also to the website designers. The business merchants can find the best way to build trust of their consumer to deal with them. Besides, the guidelines proposed will allow the website designers to develop more effective strategies in driving consumers to shop in the website. This research is within B2C e-commerce in the context of online shopping.